Transformation to the sustainable living college concept at Public University Malaysia - Buyung, Mohd Reduan; Shafii, Haryati; Yusoff, Noor Ain (Akademia Baru, 2018)
This study is a preliminary study of the transformation of residential colleges today into the concept of sustainable residential colleges in Malaysian public universities. The main problem of the study is the lack of complete guidelines to develop comfortable and conducive residential colleges. These problems lead to weaknesses and disadvantages in the provision of support facilities at residential colleges and thus sparking discomfort residents. The consequences also cause disruption to the sustainability of residential colleges and ultimately lead to the deterioration of the quality of life of the occupants. The methodology of the study is based on literature review on the elements of residential college, Maslow needs theory, facilities in residential colleges, residents' comfort, sustainable development and quality of life. The findings reveal the information of residential colleges as the basic needs of residents to live in the university, the conducive development of facilities that are conducive to academic and self-esteem, the comfort of being the priorities of the residents, sustainable development as the core concept of sustainable residential college and the impact on the quality of life of the occupants as a whole. The findings in this study will be used to assist the study of transformation of residential colleges into the concept of sustainable residential college providing complete, comfortable and conducive facilities thus leading to the improvement in the quality of life of residential colleges in Malaysian public universities.